Menguatkan Pendidikan Akhlak Anak Usia Dini melalui Peran Orangtua: Sebuah Penyuluhan - Mahfud (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service initiative was designed to enhance parents’ awareness of the importance of introducing moral education to early childhood. The program adopted a structured extension approach through counseling sessions aimed at equipping parents with both conceptual understanding and practical strategies to support their children’s character formation. The implementation followed three main stages: preparation, counseling, and evaluation. During the preparation stage, participants’ needs and parenting challenges were identified. The counseling activities were then carried out using lectures, discussions, and interactive dialogues, fostering active participation and shared learning. Evaluation was conducted through questionnaires and observation to assess participants’ comprehension and behavioral intentions. Findings indicate that parents developed a stronger awareness of their pivotal role in nurturing children’s moral values, such as honesty, discipline, respect, and empathy. Moreover, the counseling provided a reflective forum for exchanging parenting experiences. Overall, the extension approach proved effective in promoting moral education awareness and parental involvement in early childhood character building.